La contratación por horas en Colombia y su eventual afectación a los derechos laborales (2020)
Due to the economic, political, social and cultural processes, together with the volatility of the market, they make companies and public entities resort to flexible contracting modalities, which may ignore basic principles of Labor Law, especially the right to a minimum. vital, equality and job stability. The concept of hourly hiring in Colombia has been gaining strength in recent years, as an alternative that allows to counterbalance informality, reduce unemployment rates and increase coverage in the social security system, however, there are variants that they should be taken into account when making labor law more flexible. In this way, the research focuses on identifying, knowing, and studying the viability of hourly hiring in Colombia, observing the changes that have been triggered as a result of labor flexibility, and analyzing the possibility of affecting labor rights if hourly hiring is implemented in Colombia. To support the research, national and international doctrinal aspects, jurisprudence related to statistical data on the unemployment rate and informality of the Dane were taken into account. As results of the investigation it is shown that hiring by hours is a disproportionate measure that can affect labor rights.